The relationship between cognitive and moral development - Cesur, Sevim. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 1997., 1997)
The present study investigates cognitive development and the development of moral reasoning within the framework of cognitivedevelopmental theory. The theory implies that cognitive development is a necessary but not sufficient condition for moral development. In the light of the relevant theory and research, it was hypothesized that 1. Level of cognitive development is positively related to age. 2. Level of cognitive development is positively related to the level of education. 3. Level of moral development is positively related to age. 4. Level of moral development is positively related to the level of education. 5. Level of moral development is positively related to the level of cognitive development. The hypotheses were tested with subjects from the Psychology Department of Istanbul University and from the Engineering Departments of Istanbul and YiIdiz Technical Universities. Level of moral development was assessed by the Defining Issues Test (DIT) and level of cognitive development was assessed by Logical Reasoning Test (LRT). The results did not confirm the hypotheses except the second hypothesis. Although no hypothesis was developed about the effects of department and sex, post-hoc analyses revealed that engineering students and males scored higher on the LRT and psychology students and females scored higher on the DIT.
Keywords: Cognition in children.; Moral development.